the The effect of Oregon circuit training and Tabata on increasing VO2Max in male junior karate athletes at Tako Dojo Kodim 0206 Dairi in 2025: eng (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study is motivated by the low aerobic endurance (VO₂max) of junior male karate athletes at Tako Dojo Kodim 0206 Dairi, which negatively impacts their performance during competitions. The purpose of this research is to compare the effects of Oregon Circuit Training and Tabata to determine which method is more effective in improving VO₂max, thereby optimizing the performance of karate athletes. The research methodology employs an experimental design to examine the effects of treatments on samples under controlled conditions (Sugiyono, 2013:74). The study was conducted in two testing phases: a pretest to obtain initial data and a posttest after implementing a training program consisting of 16 sessions, aimed at measuring the effectiveness of the exercises on improving participants' abilities.The results of the study based on statistical analysis using SPSS 25 with a paired sample t-test showed that Oregon circuit training significantly increased VO2Max with a Sig value of 0.001 < (0.05), while Tabata training also had a significant effect with a Sig value of 0.003 < (0.05). Furthermore, the results of the independent sample T-test showed a Sig value of 0.404 > (0.05), which means there was no significant difference between the effectiveness of the two training methods.Furthermore, the results of the independent sample t-test showed a Sig value of 0.404 > (0.05), indicating no significant difference in the effectiveness of the two training methods. Based on the research results, it can be concluded that both Oregon Circuit Training and Tabata training have a significant effect on increasing the VO2Max of junior male karate athletes at the Tako Dojo Kodim 0206 Dairi in 2025. However, there is no significant difference between the two, so both training methodsre equally effective in improving VO2Max